2004
DOI: 10.1080/01926230490462138
|View full text |Cite
|
Sign up to set email alerts
|

Bone Neoplasms in F344 Rats Given Teriparatide [rhPTH(1-34)] Are Dependent on Duration of Treatment and Dose

Abstract: A long-term study was conducted in female F344 rats to determine the relative importance of dose, treatment duration, and age at initiation of treatment on the incidence of teriparatide [rhPTH[1-34)]-induced bone proliferative lesions. Treatment groups consisted of different combinations of dose (0, 5, or 30 microg/kg/d), treatment duration (6, 20, or 24 months) and age at initiation of treatment (2 or 6 months of age). The primary endpoints were the incidence of bone neoplasms and effects on bone mass and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
203
3
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 332 publications
(215 citation statements)
references
References 29 publications
3
203
3
3
Order By: Relevance
“…Moreover, the doses employed were large multiples (threefold to 58-fold) of the human dose. (2) The second rat carcinogenicity study by Vahle and colleagues (55) confirmed that the development of bone neoplasm in rats was strongly dependent on the dose and the duration of treatment, whereas the age at initiation had only a minor effect. Consistent findings were reported in the PTH(1-84) study, which examined Fisher 344 rats given doses of 10, 50, or 150 mg/kg/d for 24 months.…”
Section: Osteosarcomamentioning
confidence: 95%
See 4 more Smart Citations
“…Moreover, the doses employed were large multiples (threefold to 58-fold) of the human dose. (2) The second rat carcinogenicity study by Vahle and colleagues (55) confirmed that the development of bone neoplasm in rats was strongly dependent on the dose and the duration of treatment, whereas the age at initiation had only a minor effect. Consistent findings were reported in the PTH(1-84) study, which examined Fisher 344 rats given doses of 10, 50, or 150 mg/kg/d for 24 months.…”
Section: Osteosarcomamentioning
confidence: 95%
“…(2,3,55,56) In the United States, the FDA identifies major safety concerns with a ''black box'' warning, a designation given to teriparatide with specific reference to osteosarcoma. The labeling instructions contraindicate the use of teriparatide in any situation in which the risk of osteosarcoma is increased.…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations